Flight 19 : lost in the Bermuda Triangle - Bowman, Chris, 1990-; Yotter, Tate. (2020)
"Exciting illustrations follow the events of the disappearance of Flight 19. The combination of brightly colored panels and leveled text is intended for students in grades 3 through 7"--
Clear skies -- In trouble -- Lost! -- Searching for answers -- Theories behind the disappearance.
Includes bibliographical references and index.
Ages 8-13
Keywords: Aircraft accidents -- Bermuda Triangle -- Juvenile literature; Bermuda Triangle -- Juvenile literature